La estructura agraria en América Latina Un modelo de análisis - Dandler, Jorge; Havens, A. Eugene; Samaniego, Carlos; Sorj, Bernardo (Revista Mexicana de Sociología, 2024)
La estructura agraria en América Latina Un modelo de análisis.